EGFR/TGFα and TGFβ/CTGF signaling in neuroendocrine neoplasia: theoretical therapeutic targets - Kidd, Mark; Schimmack, Simon; Lawrence, B.; Alaimo, D.; Modlin, I. M. (Neuroendocrinology, 2013)
Neuroendocrine neoplasms (NENs) are a heterogeneous family of malignancies whose proliferation is partially dependent on growth factors secreted by the microenvironment and the tumor itself. Growth factors which were demonstrated to be important in experimental models of NENs include EGF (epidermal growth factor), TGF (transforming growth factor) α, TGFβ and CTGF (connective tissue growth factor). EGF and TGFα bind to the EGF receptor to stimulate an intact RAS/RAF/MAPK pathway, leading to the transcription of genes associated with cell proliferation, invasion and metastasis. Theoretically, TGFα stimulation can be inhibited at several points of the MAPK pathway, but success is limited to NEN models and is not evident in the clinical setting. TGFβ1 stimulates TGFβ receptors (TGFβRI and TGFβRII) resulting in inhibition of neuroendocrine cell growth through SMAD-mediated activation of the growth inhibitor P21WAF1/CIP1. Although some NENs are inhibited by TGFβ1, paradoxical growth is seen in experimental models of gastric and small intestinal (SI) NENs. Therapeutic targeting of TGFβ1 in NENs is therefore complicated by uncertainty of the effect of TGFβ1 secretion on the direction of proliferative regulation. CTGF expression is associated with more malignant clinical phenotypes in a variety of cancers, including NENs. CTGF promotes growth in gastric and SI-NEN models, and is implicated as a mediator of local and distant fibrosis caused by NENs of enterochromaffin cell origin. CTGF inhibitors are available, but their anti-proliferative effect has not been tested in NENs. In summary, growth factors are essential for NEN proliferation, and although interventions targeting these proteins are effective in experimental models, only limited clinical efficacy has been identified.